Systemic lymphangitic carcinomatosis from unknown primary cancer mimicking lung disease in a new coronavirus infection (COVID-19): a case report - E. S. Andryukhova; N. V. Krakhmal; L. A. Tashireva; S. V. Vtorushin; M. V. Zavyalova; V. M. Perelmuter (Сибирский онкологический журнал)
lymphangitic carcinomatosis is characterized by the spread of cancer cells through pulmonary lymphatic vessels, which results in secondary interstitial inflammation. The diagnosis of lymphangitic carcinomatosis is challenging due to nonspecific clinical symptoms and radiological findings that similar to those of interstitial lung disease.The purpose of the study was to demonstrate difficulties in the diagnosis of lymphangitic carcinomatosis with a systemic dissemination from unknown primary site. Case presentation. We report on a case of lymphangitic carcinomatosis from cancer of unknown primary origin with systemic involvement of internal organs imitating pulmonary disease caused by coVid-19. patient K., 58 years old, was treated for 12 bed-days in therapy departments with the diagnosis of bilateral viral coVid-19 pneumonia. clinical, laboratory and instrumental data were nonspecific. despite treatment, heart failure and kidney disease progressed to terminal stages, leading to the death of the patient. Autopsy revealed systemic lymphangitic carcinomatosis from cancer of unknown primary origin with involvement of the lungs, heart, liver, pancreas, spleen, kidneys and adrenal glands. lymphangitic carcinomatosis mimicked interstitial lung disease in a novel coronavirus infection coVid-19. metastasis to the heart mimicked coronary disease, and metastases to the kidneys led to acute kidney failure, which along with acute respiratory and heart failure caused the death of the patient.Conclusion. lymphangitic carcinomatosis, which does not have specific clinical manifestations, is able to mimic interstitial lung diseases, including a new coronavirus infection. cancer of unknown primary and multiple visceral metastases in this case confirm the concept of the independence of different types of tumor progression.